Expression and Possible Role of Silent Mating Type Information Regulation 2 Homolog 1 in Post-necrotizing Enterocolitis Stricture in vivo and in vitro - Chen, Rui; Lv, Chengjie; Zhao, Yun; Gu, Weizhong; Zhang, Luyin; Shi, Bo; Tou, Jingfa (Frontiers in Pediatrics, 2022)
Purpose To investigate the expression and possible role of Sirtuin1 or Silent mating–type information regulation 2 homolog-1 (SIRT1) in post-necrotizing enterocolitis stricture. Materials and Methods The expression characteristics of SIRT1 and TGF-β1 in post-necrotizing enterocolitis stricture were detected by immunohistochemistry. The siRNA-SIRT1 was used to inhibit the expression of SIRT1 in intestinal epithelial cells-6 (IEC-6), and qRT-PCR, WB, and ELISA were utilized to detect the changes of Transforming growth factor-β1 (TGF-β1), nuclear factor (NF)-κB, tumor necrosis factor-α (TNF-α), tight junction protein-1 (ZO-1), and vascular endothelial growth factor (VEGF) expressions. The IEC-6 cell proliferation and migration ability were tested via CCK8 kit and Transwell test. The expression of E-cadherin and Vimentin in cells was detected by immunofluorescence. Results The CRP, IL-6, IL-10, and IFN-γ in the serum of Necrotizing enterocolitis (NEC) intestinal stenosis patients were significantly higher than the reference values. The SIRT1 protein was under-expressed and the TGF-β1 protein was overexpressed in NEC intestinal stenosis tissue. And the expression of SIRT1 was negatively correlated with TGF-β1. At the time of diagnosis of NEC, the expression of SIRT1 decreased in children with respiratory distress syndrome and CRP level increased. After inhibiting the expression of SIRT1 in IEC6 cells, the expression levels of TGF-β1, Smad3, and NF-κB were decreased, and the expression of ZO-1 was also decreased. The proliferation and migration ability of IEC6 cells was decreased significantly, and the expression of E-cadherin and Vimentin proteins in IEC6 cells did not change significantly. Conclusion Promotion of intestinal fibrosis by inflammation may be the mechanism of post-necrotizing enterocolitis stricture. SIRT1 may be a protective protein of NEC. The probable mechanism is that SIRT1 can regulate intestinal fibrosis and can protect the intestinal mucosal barrier function to participate in the process of post-necrotizing enterocolitis stricture.